QSM-detected iron accumulation in the cerebellar gray matter is selectively associated with executive dysfunction in non-demented ALS patients - Aiello, Edoardo Nicolò; Contarino, Valeria Elisa; Conte, Giorgio; Solca, Federica; Curti, Beatrice; Maranzano, Alessio; Torre, Silvia; Casale, Silvia; Doretti, Alberto; Colombo, Eleonora; Verde, Federico; Silani, Vincenzo; et al. (Frontiers in Neurology, 2024)
Background. This study aimed at assessing whether quantitative susceptibility imaging (QSM)-based measures of iron accumulation in the cerebellum predict cognitive and behavioural features in non-demented ALS patients. Methods. N=61 ALS patients underwent 3-T MRI and a clinical assessment via the ALS Functional Rating-Scale Revised (ALSFRS-R) and Edinburgh Cognitive and Behavioural ALS Screen (ECAS). Regression models were run on each subscale of the cognitive section of the ECAS and on the ECAS-Carer Interview in order to test the effect of QSM-based, white and gray matter (WM; GM) cerebellar measures – separately for right, left and bilateral cerebellar ROIs – as compared to that of WM/GM, right and left cerebellar volumetrics by covarying for demographics, disease status and total intracranial volume. Results. Higher left- and right-sided, as well as bilateral QSM measures of the cerebellar GM selectively predicted (ps≤.003) a higher number of errors on the Executive Functioning (EF) subscale of the ECAS (ECAS-EF). Moreover, higher GM-related, QSM-based measures of the cerebellum predicted a higher probability of a below-cut-off ECAS-EF performance (ps≤.024). Neither QSM-based measures of the cerebellar WM, nor volumetric ones, yielded any significant effect on the ECAS-EF. No effects were detected as to other ECAS measures. Backward digit span and Social cognition tasks selectively predicted by bilateral QSM measures of the cerebellar GM. Discussion. Iron accumulation within the cerebellar GM – i.e., cerebellar cortices – may be associated with EF deficits in non-demented ALS patients. QSM-based measures are potentially useful for unraveling the neural correlates of cognitive deficits in ALS.